2021
DOI: 10.3390/jcm10081637
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of the Test of Orthorexia Nervosa (TON-17)

Abstract: This study aims to develop and validate a new self-report questionnaire to measure orthorexia nervosa (ON). Based on a current review of the scientific literature and interviews with people at risk of orthorexia, 40 items were selected to test orthorexia nervosa (TON-40). A total sample of 767 individuals (M = 26.49, SD = 9.66, 56.98% women) participated in the study. The exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and composite construct analysis (CCA) were performed to find an appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(36 citation statements)
references
References 84 publications
2
34
0
Order By: Relevance
“…Orthorexia was measured with a 17-item Test of Orthorexia Nervosa (TON-17) questionnaire, with a response scale ranging from 1 (totally disagree) to 5 (totally agree) [47]. All items form a general score (by addition) and can also be divided into three subscales: control of food quality (CFQ), fixation on health and healthy lifestyle (FHHL), and disorder symptoms (DS).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Orthorexia was measured with a 17-item Test of Orthorexia Nervosa (TON-17) questionnaire, with a response scale ranging from 1 (totally disagree) to 5 (totally agree) [47]. All items form a general score (by addition) and can also be divided into three subscales: control of food quality (CFQ), fixation on health and healthy lifestyle (FHHL), and disorder symptoms (DS).…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence of orthorexia depends on the diagnostic cut-off criteria, the instrument used, or geographic region, and ranges between 1% to 89%, as suggested by review studies [43][44][45]. However, Varga et al [45] found the average prevalence of ON to be 6.9% in the general population, while rates between 1% and 7% were estimated by using Düseldorf Orthorexia Scale (DOS ≥ 30) [46], and 5.5% using Test of Orthorexia Nervosa (TON-17 ≥ 61) [47] in the Polish sample. However, the prevalence of ON was rarely assessed among university students.…”
Section: Orthorexia Nervosamentioning
confidence: 99%
See 1 more Smart Citation
“…Barbanti [39] was the only study that applied the Bratman Orthorexia Test (BOT) [2]. None of the studies used the more recently developed ORTO-R [43], the Test of Orthorexia Nervosa (TON-17) [44], the Orthorexia Nervosa Inventory (ONI) [45], the Barcelona Orthorexia Scale (BOS) [46], the Düsseldorf Orthorexia Scale (DOS) [47], the Eating Habits Questionnaire (EHQ) [48], or the Teruel Orthorexia Scale [49].…”
Section: Tools Used To Identify On Tendenciesmentioning
confidence: 99%
“…After a structural analysis, the number of items was reduced from 40 to 17 (TON-17), including three subscale factors (Control of food quality, Fixation of health and healthy diet, and Disorder symptoms) in a hierarchical, bi-factor structure. The study demonstrates that the TON-17 scale has good psychometric properties, stability, reliability, and construct validity, and therefore it could become a promising tool for assessing the risk of orthorexia nervosa [1].…”
mentioning
confidence: 85%